Isolation, Characterization, and Anti-Allergic Evaluation of Phytochemicals from Wikstroemia trichotoma - Keem, Min-Ji; Kim, Tae-Young; Park, No-June; Choi, Sangho; Paik, Jin-Hyub; Jo, Beom-Geun; Kwon, Taek-Hwan; Kim, Su-Nam; Lee, Seoung Rak; Yang, Min Hye (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: The Wikstroemia genus has been traditionally used in Asia to treat various ailments, including parotitis, pneumonia, and pertussis. These plants contain many bioactive compounds, including flavonoids, coumarins, and lignans. This study investigates the chemical components of a MeOH extract of the aerial parts of Wikstroemia trichotoma (Thunb.) Makino and evaluates their anti-inflammatory and anti-allergic effects in vitro. Methods: Chromatographic techniques, spectroscopic analysis, and the literature were used to isolate compounds from the branches and leaves of W. trichotoma. IL-4 mRNA and beta-hexosaminidase levels were assessed by performing assays on RBL-2H3 cells to evaluate anti-inflammatory and anti-allergic potential. Results: Forty-two compounds were isolated from the W. trichotoma extract, and the flavanones trichotocinol A and B were newly identified. Screening of isolated compounds showed that several significantly inhibited DNP-BSA-induced beta-hexosaminidase release by 10.0-58.0% and PMA/ionomycin-induced IL-4 mRNA expression by 25.3-71.7% versus negative controls. In addition, trichotocinol A reduced IL-4 mRNA expression by 31.9%. Conclusions: The discovery of these new compounds contributes to our understanding of the bioactive properties of W. trichotoma and suggests their potential use as natural therapeutic agents for inflammatory disorders.